Persepsi Mahasiswa terhadap Lahjah Arab Penutur Non-Native: Analisis Sosiolinguistik: Persepsi Dialek Arab Non-Asli di Kalangan Mahasiswa Indonesia: Sebuah Studi Sosio-Linguistik - Fatia Rahmanita; Maryam Nur Annisa; Holis; Syaiful Mustofa (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Arabic, as a global language, is learned by students across Indonesia who bring diverse linguistic and cultural backgrounds. These differences influence pronunciation, identity expression, and interaction dynamics, particularly when non-native dialects emerge in academic communication. Purpose: This study analyzes Indonesian graduate students’ perceptions of non-native Arabic dialects, focusing on linguistic variation, social interaction, cultural identity, and academic social norms. Method: This qualitative case study involved five graduate students from Aceh, Java, Bone, Maluku, and Madura. Data were collected through semi-structured interviews conducted over two weeks. Thematic analysis following Braun & Clarke’s (2006) six-phase model was used, supported by member checking to ensure credibility. Result and Discussion: Students viewed dialect variation as a natural reflection of cultural diversity. Some reported challenges in understanding pronunciation differences, while others perceived interactions across dialects as enriching and supportive of linguistic tolerance. Academic norms still prioritize fushah Arabic, yet students’ regional identities remain evident in their speech.. Conclusions and Implications: This study findings highlight the importance of integrating sociolinguistic awareness into Arabic curricula to improve cross-dialect communication competence, cultural sensitivity, and inclusive learning practices